Foraminiferal biostratigraphy of Early Cretaceous (Hauterivian-Barremian) sediments of the Zagros basin (SW of Iran). (September 2016) - Afghah, Massih; Abtahiyan, Ali-Reza; Saberi, Amir
Abstract: Parts of Early Cretaceous sediments of the Zagros basin (SW of Iran) is nominated as the Gadvan Formation. To facilitate biostratigraphy study, four stratigraphic sections of this rock unit are selected around Shiraz named as Fahliyan, Kamal abad, Garm abad, and Hossien abad stratigraphic columns. These stratigraphic sections are sandwiched between the Fahliyan and Dariyan formations. Foraminiferal biostratigraphy of these sections have supported two biozones in the three of studied sections and one section is marked by one biozone. Normally established biozones of the studied section are described as Pseudocyclammina lituus – Trocholina assemblage zone (Hauterivian) and Choffatella decipiens– Praechrysalidina infracretacea assemblage zone (Barremian). Two established biozones are recognizable in Fahliyan, Garm abad, and Kamal abad stratigraphic sections as Hauterivian to Barremian age and Hossien abad stratigraphic section is described by one which marks Barremian. Biostratigraphy of the studied stratigraphic sections of the Gadvan reveals different lower biostratigraphic limit whereas; the upper biostratigraphic limit of the Gadvan is synchronous across the entire studied area. Biostratigraphic data of studied stratigraphic sections fully supported the dominant agglutinated foraminifera in Gadvan Formation. Also dasycladacea are recorded in all the studied stratigraphic sections. Graphical abstract: Highlights: New age determination of the Gadvan Formation is distinguished by identification of benthic Foraminifera. This work confirms new foraminifer association. This study supports well developed calcareous algae of Hautrivian- Barremian strata. stratigraphic distribution of investigated foraminifers reveals new Gadvan biozones.